Densification and mechanical properties of boron carbide prepared via spark plasma sintering with cubic boron nitride as an additive. Issue 4 (April 2020) - Sun, Jinchang; Niu, Bo; Ren, Lin; Zhang, Jinyong; Lei, Liwen; Zhang, Fan
Abstract: Hexagonal boron nitride ( h -BN) can reinforce boron carbide (B4 C) ceramics, but homogeneous dispersion of h -BN is difficult to achieve using conventional methods. Herein, B4 C/ h -BN composites were manufactured via the transformation of cubic ( c -) BN during spark plasma sintering at 1800 °C. The effects of the c -BN content on the microstructure, densification, and mechanical properties of B4 C/ h -BN composites were evaluated. In situ synthesized h -BN platelets were homogeneously dispersed in the B4 C matrix and the growth of B4 C grains was effectively suppressed. Moreover, the c -BN to h -BN phase transformation improved the sinterability of B4 C. The sample with 5 vol.% c -BN exhibited excellent integrated mechanical properties (hardness of 30.5 GPa, bending strength of 470 MPa, and fracture toughness of 3.84 MPa⋅ m 1/2 ). Higher c -BN contents did not significantly affect the bending strength and fracture toughness but clearly decreased the hardness. The main toughening mechanisms were crack deflection, crack bridging, and pulling out of h -BN.